A Wireless Pressure Measurement System Using a SAW Hybrid Sensor - Schimetta, Gernot; Dollinger, Franz; Weigel, Robert (IEEE MTT-S Microwave Symposium, 2000)
A pressure-measurement system based on surface-acoustic-wave (SAW) sensors is presented in this paper. Since SAW sensors are powered by the energy of the RF field, no battery is required, which is a major drawback of conventional microcontroller-based telemetry systems. A successful combination of a SAW reflective delay line with a high-Q capacitive pressure sensor is shown, With a new way of matching the sensor impedance to the SAW reflector impedance, both a high signal-to-noise ratio and a high signal dynamic are achieved, which supports accurate signal evaluation. As an example of realization, the prototype of the pressure sensor unit is presented
elib2cris::1512001600,schimetta2000
Keywords: SAW; Sensor